2019
DOI: 10.1016/j.jcp.2019.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Causality and Bayesian Network PDEs for multiscale representations of porous media

Abstract: Microscopic (pore-scale) properties of porous media affect and often determine their macroscopic (continuum-or Darcy-scale) counterparts. Understanding the relationship between processes on these two scales is essential to both the derivation of macroscopic models of, e.g., transport phenomena in natural porous media, and the design of novel materials, e.g., for energy storage. Most microscopic properties exhibit complex statistical correlations and geometric constraints, which presents challenges for the esti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Such predictions are nonintuitive. While previous work found that parametric-based microscale uncertainties can be dampened in multiscale models (43), the results of this work will generalize to any models where finescale simulations (such as DFT) are sparse or the macroscale QoIs can be made proportional to the microscale properties. In the next section, we show that Eq.…”
Section: Model Uncertainty Guarantees Nonparametric Sensitivity Anmentioning
confidence: 79%
“…Such predictions are nonintuitive. While previous work found that parametric-based microscale uncertainties can be dampened in multiscale models (43), the results of this work will generalize to any models where finescale simulations (such as DFT) are sparse or the macroscale QoIs can be made proportional to the microscale properties. In the next section, we show that Eq.…”
Section: Model Uncertainty Guarantees Nonparametric Sensitivity Anmentioning
confidence: 79%
“…In that case, singular‐value decomposition techniques, such as a truncated Karhunen‐Loève transformation, are used to approximate p with a set of M ( M ≪ M par ) mutually uncorrelated identically distributed random variables ξ ={ ξ 1 ,…, ξ M }. Alternatively, if p ={ p 1 ,…, p M } represents M par = M correlated random variables (rather than random fields), then the Rosenblatt transform (e.g., section 4.1 in Um et al., ) maps p onto a set of random variables ξ ={ ξ 1 ,…, ξ M } that are independent and identically distributed on the interval (0,1).…”
Section: Methodsmentioning
confidence: 99%
“…This renders it inapplicable, except as an uncontrollable approximation, to hydrologic systems, whose parameters are often correlated random fields and are cross-correlated with each other. Such problems call for the use of moment-independent GSA techniques, including distribution-based GSA (Borgonovo, 2007), a PCE-based method of Caniou and Sudret (2011), and Bayesian nets (Um et al, 2019). Yet hydrologic applications of moment-independent GSA accelerated by PCE-based surrogates remain scarce (e.g., Rajabi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Note that in case of correlated input parameters one has to preliminary transform p onto a set of independent random variables to derive the PCE approximation (e.g., Section 4.1 in Um et al, 2019).…”
Section: Global Sensitivity Analysismentioning
confidence: 99%